ANALISA PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN DENGAN METODE DU PONT - Malfin Zainul Fanani; Eko Widodo; Heru Sutapa; Syaiful Ahmad (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This research was conducted at automotive and component manufacturing companies listed on the Indonesia Stock Exchange at PT Gajah Tunggal Tbk and PT Multistrada Arah Sarana Tbk for the period 2015 - 2019. The purpose of this study was to determine the company's financial performance at PT Gajah Tunggal Tbk and PT Multistrada Arah. Sarana Tbk in 2015-2019 using the Du Pont System method and what factors affect differences in financial performance. This research uses descriptive quantitative research methods and data analysis techniques using the du pont method. The data used in this research is the financial statement data of the companies PT Gajah Tunggal Tbk and PT Multistrada Arah Sarana Tbk for the last five years in 2015-2019. The results of the research that has been done show that the financial statements of PT Gajah Tunggal Tbk and PT Multistrada Arah Sarana Tbk for five years, the authors can conclude that based on the average Return On Assets (ROA), the average Net Profit Margin (NPM), and the average Total Assets Turn Over (TATO), during 2015-2019 shows that PT Gajah Tunggal Tbk, has a better financial performance than PT Multistrada Arah Sarana Tbk. As for the factors causing the decline in the value of TATO, NPM and ROA, namely the decrease in net income due to the influence of total costs and the company's ineffectiveness in managing existing assets, so that the profit resulting from the comparison of the value of net income to total assets is very small.